2022
DOI: 10.1002/adts.202200244
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Quantum Chemical Characterization of the Astrochemically Relevant HCnH Chain Family: An Attempt to Aid Astronomical Observations

Abstract: In this paper, the results of a comprehensive theoretical investigation of neutral HC n H 0 and charged HC n H ± chains are reported using state-of-the-art compound model chemistries (W1BD, G4, CBS-QB3, CBS-APNO, CBS-4M) and single point methods (including "gold standard" CCSD(T)). The properties envisaged include electronic and chemical bonding structure data, enthalpies of formation, adiabatic and vertical ionization (IP), and electron attachment (EA) energies, gas phase acidities, C−H bond strengths, and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

7
0

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 113 publications
1
20
0
Order By: Relevance
“…Tables 1, S2, and S3) we performed unrestricted (UB3LYP) calculations. Therefore, it is worth mentioning that, similar to other similar cases [19, 20, 21, 22], we can safely rule out spin contamination artifacts (cf. Table 1).…”
Section: Computational Detailssupporting
confidence: 65%
“…Tables 1, S2, and S3) we performed unrestricted (UB3LYP) calculations. Therefore, it is worth mentioning that, similar to other similar cases [19, 20, 21, 22], we can safely rule out spin contamination artifacts (cf. Table 1).…”
Section: Computational Detailssupporting
confidence: 65%
“…BDE for H-atom abstraction at positions 1-OH, 2-OH, and 3-OH in ATV, o-ATV and p-ATV is basically the same. The differences between the values calculated by us for ATV, o-ATV, and p-ATV amounting to at most 0.5 kcal/mol are certainly irrelevant; recall that we showed recently [20] that even for much smaller molecules in vacuo DFT/B3LYP calculations with the largest Pople basis set 6-311++G(3df,3pd) are far away from “chemical” accuracy (∼ 1 kcal/mol). In fact, p-ATV’s numerical value of PA=58.2 kcal/mol somewhat differs from ATV’s (and o-ATV’s) PA=61.5 kcal/mol, but if heterolytic O-H bond cleavage were to occur in p-ATV, it would rather occur at position 1-OH, which has a substantially smaller value PA=23.8 kcal/mol.…”
Section: Resultsmentioning
confidence: 80%
“…From experience with much smaller molecules and much simpler chemical structures (e.g., ref. [ 20 ]) we had to learn that achieving this accuracy for bond dissociation enthalpies and proton affinity (BDE and PA, quantities entering the discussion that follows) is often illusory even for extremely computationally demanding state-of-the-art compound model chemistries (CBS-QB3, CBS-APNO, G4, W1BD); see, e.g., Figure 10 of ref. [ 20 ].…”
Section: Computational Detailsmentioning
confidence: 99%
“…[ 20 ]) we had to learn that achieving this accuracy for bond dissociation enthalpies and proton affinity (BDE and PA, quantities entering the discussion that follows) is often illusory even for extremely computationally demanding state-of-the-art compound model chemistries (CBS-QB3, CBS-APNO, G4, W1BD); see, e.g., Figure 10 of ref. [ 20 ]. DFT-calculations done by us and by others [ 21 ] revealed that, e.g., errors in ionization potential can amount up to 0.7 eV (16 kcal/mol) even when employing the functional B3LYP and the largest Pople basis set 6-311++G(3df,3pd).…”
Section: Computational Detailsmentioning
confidence: 99%